2015
DOI: 10.1136/jech-2014-204781
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic regulation of Newborns’ imprinted genes related to gestational growth: patterning by parental race/ethnicity and maternal socioeconomic status

Abstract: Background Children born to parents with lower income and education are at risk for obesity and later-life risk of common chronic diseases, and epigenetics has been hypothesised to link these associations. However, epigenetic targets are unknown. We focus on a cluster of well-characterised genomically imprinted genes because their monoallelic expression is regulated by DNA methylation at differentially methylated regions (DMRs), are critical in fetal growth, and DNA methylation patterns at birth have been asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 73 publications
2
53
1
1
Order By: Relevance
“…Results of the relationship between maternal socioeconomic status and infants' methylation age demonstrate that SES was negatively and significantly associated with methylation age at birth ( r s = −0.48, P s = 0.005). Findings from King et al [32] suggest that epigenetics may relate the lower maternal socioeconomic status to adverse obstetrical outcomes (i.e., low birth weight) and even adult-onset chronic diseases and conditions (i.e., obesity, diabetes, cardiovascular diseases, and cancers). Therefore, further studies are needed to explore epigenome responses to environment of our human society, laying great emphasis on the importance of early-life experience.…”
Section: Discussionmentioning
confidence: 99%
“…Results of the relationship between maternal socioeconomic status and infants' methylation age demonstrate that SES was negatively and significantly associated with methylation age at birth ( r s = −0.48, P s = 0.005). Findings from King et al [32] suggest that epigenetics may relate the lower maternal socioeconomic status to adverse obstetrical outcomes (i.e., low birth weight) and even adult-onset chronic diseases and conditions (i.e., obesity, diabetes, cardiovascular diseases, and cancers). Therefore, further studies are needed to explore epigenome responses to environment of our human society, laying great emphasis on the importance of early-life experience.…”
Section: Discussionmentioning
confidence: 99%
“…31 Psychosocial pathways and early lifetime physical disadvantages, for example, low birth weight, 8 resulting in epigenetic modifications, may offer further explanations. 32 Strengths of our study include a reliable diagnosis of stroke not only depending on self-reported stroke, hospital discharge data, or stroke mortality as in some previous studies, 6,[8][9][10][11][12]14 and subgroup analyses of stroke pathogenesis. Furthermore, we assessed a wide range of items characterizing socioeconomic status particularly in childhood, in contrast to previous studies that had relied on one parameter only, mainly paternal or parental profession, 10,12,13,15,16 sometimes also on educational attainment, 6,14 number of siblings, 9 or housing conditions.…”
Section: Strokementioning
confidence: 99%
“…There are racial differences in the epigenetic profiles of newborns, 28 including in regions associated with growth and obesity. 29 Recent studies suggest that mode of delivery is associated with different methylation patterns in infants. 17,18 If epigenetic changes that are associated with delivery mode vary by race in a way that influences weight and/or growth, this could also explain the race-specific association of CS on risk of obesity.…”
Section: Race C-section and Childhood Obesity -Cassidy Et Almentioning
confidence: 99%
“…27 There are racial differences in epigenetic patterns (ie, DNA methylation) present at birth, 28 including racial differences in methylation at regions known to impact growth and obesity risk. 29 Epigenetic changes in cord blood DNA are associated with body size in childhood. 30 There is growing evidence that mode of delivery is associated with epigenetic changes in the both the placenta and the infant.…”
Section: Introductionmentioning
confidence: 99%